ANALISIS STRATEGI MARKETING COMMUNICATION MELALUI NAMING RIGHTS DI STASIUN MRT: CIPETE RAYA TUKU - Hilda Risca Chairanti; Guruh Ramdani (Universitas Merdeka Madiun, 2025)
This service activity aims to analyze marketing communication strategies thru the naming rights practice implemented by the TUKU brand at Cipete Raya MRT Station. Naming rights is a marketing strategy that grants companies the right to name public facilities with the aim of building exposure and brand image. This activity uses a quantitative approach by distributing questionnaires to 87 MRT users. This service activity found that the naming rights strategy contributed to an increase in brand awareness by 78.2% and public perception by 81.4%. The results of the validity and reliability tests indicate that all instrument items are valid and reliable. Additionally, the results of the normality and linearity tests show that the data is normally distributed and has a significant relationship between variables. The results of this study indicate that the marketing communication strategy thru naming rights is effective in expanding brand recognition and creating a better public perception of TUKU. Collaboration with MRT Jakarta successfully made TUKU a part of the daily lives of urban residents. This strategy proves effective in creating consumer engagement and strengthening brand image thru the integration of branding in public spaces.